Case Report: Management of an Elderly Patient With Metastatic Radioiodine-Resistant Differentiated Thyroid Cancer in a Rural Community, Remote From Specialist Oncology Services - Wybrew, Rachael; Loynd, Michael; Wybrew, Maria; Samuel, Leslie (Frontiers in Endocrinology, 2021)
This case report describes an elderly patient with radioiodine-resistant differentiated thyroid cancer and additional multiple metastases living in a rural setting, remote from the specialist oncology service. This case is of interest because effective systemic therapies for treatment-resistant cancers, such as lenvatinib, are now available but can potentially cause significant toxicities that require extensive medical management. Here, we discuss how patient care was provided collaboratively by the local community teams integrated with remote specialist oncology services. A 77-year-old patient presented with symptoms of cauda equina secondary to a large metastatic sacral deposit. The deposit was biopsied, and histology revealed a diagnosis of differentiated follicular thyroid cancer that was treated with external beam radiotherapy and thyroidectomy, followed by radioiodine. However, the disease was found to be resistant to radioiodine therapy, and the patient subsequently developed back pain due to new bone metastases. After further palliative external beam radiotherapy, the patient was started on systemic treatment with lenvatinib. Treatment has continued for more than 2.5 years with a slow but steady improvement in symptoms and quality of life. Monitoring and assessment of lenvatinib therapy and management of associated toxicities was coordinated remotely from a specialist cancer center over 200 miles away, using the skills of the local medical and nursing teams. This case report demonstrates how a cooperative effort using local teams and video-conferencing links to a specialist cancer center can be applied to safely treat a patient with a medication that may result in significant potential toxicities that require attentive and dynamic management.